Water-deficit tolerance of landrace and improved corn genotypes - Langne, Josana Andreia; Lago, Isabel; Reiniger, Lia Rejane Silveira; Petry, Mirta Teresinha; Streck, Nereu Augusto; Durigon, Angelica; Pohlmann, Valeria; Freitas, Charles Patrick de Oliveira de; Slim, Taís; Silva, Stefanía Dalmolin da (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the yield, leaf area, stomatal conductance, photosynthesis, transpiration, and critical fraction of transpirable soil water (FTSWc) of hybrid and landrace corn (Zea mays) genotypes, as affected by the water deficit characterized by the FTSW. Two experiments were carried out in the 2015/2016 and 2016/2017 crop years: one in the field and the other in a greenhouse. The following genotypes were evaluated in irrigated and nonirrigated systems: the Cinquentinha and Bico de Ouro landraces and the AS 1573PRO improved cultivar. Yield in the field was higher for 'AS 1573PRO', followed by Bico de Ouro and Cinquentinha in both evaluation years. Water deficit reduces stomatal opening, photosynthesis, and transpiration rate, resulting in the total closure of the stomata of 'AS 1573PRO' and Bico de Ouro, and in the partial closure of those of Cinquentinha. There was a reduction in the leaf area of 'AS 1573PRO', Bico de Ouro, and Cinquentinha under water deficit during the reproductive period. In the first crop year under water deficit conditions, 'AS 1573PRO' and Cinquentinha show a high tolerance to water deficit with a FTSWc of 0.71, and 'AS 1573PRO' also shows the highest tolerance in the second crop year with a FTSWc of 0.73. Moreover, Bico de Ouro is sensitive to water deficit in the two crop years.